Helping the Transition: Mentorship to Support International Students in Canada - Thomson, Clint; Esses, Victoria M. (Journal of International Students, 2016)
We developed a program that paired newcomer international students with Canadian student mentors. These pairs met weekly throughout a semester and international student participants completed measures at both the beginning and end of the program. We found that program participants experienced positive changes in sociocultural and psychological adaptation, and a reduction in acculturative stress over time. At the conclusion of the program, program participants also showed higher levels of psychological adaptation and lower levels of acculturative stress than control participants, who had not participated in the program. These findings make an important contribution to the empirical literature on the acculturation of international students and provide foundations for future research.